Synthetic Osteogenic Matrix using Polymeric Dendritic Peptides for treating Human Periodontal defects – design and in vitro evaluation. (2019) - Das, Eva C.; Babu, Jisha; Dhawan, Sameer; Kumar PR, Anil; Kumary, T.V.; Haridas, V.; Komath, Manoj
Abstract: Functional peptide molecules or their component functional moieties can be appended to self assembling polymers to mimic the extracellular matrix (ECM) and bring about predictable cell responses. Terminal guanidine functional group renders positive charge to the amino acid arginine, a component of the cell adhesive peptide Arginylglycylaspartic acid (RGD). We present the design and synthesis of guanidine appended polydiacetylene (G-PDA) as a cell adhesive matrix. Human periodontal ligament cell adhesion and differentiation on G-PDA matrix was evaluated to assess the feasibility of using the matrix for endogenous cell homing in periodontal regeneration. Guanidine appended polydiacetylene matrix proves to be a good substrate for cell homing, proliferation and differentiation. A well-designed scaffold using this material can lead to the regeneration of the periodontal bone.